Estudo comparativo entre pacientes com esofagite erosiva e com esôfago de barrett por meio de impedância/phmetria prolongada do esôfago - Marcela Penna Soares (2009)
Gastroesophageal reflux disease (GERD) shows a large spectrum of clinical presentations, wich includes non erosive disease, erosive esophagitis and complicated forms, such as Barrett esophagus (BE). BE is the condition in which abnormal colunnar epithelium replaces the stratified squamous epithelium that normally lines the distal esophagus. This condition is considered the main risk factor for esophagus adenocarcinoma development. Several attempts were done trying to find which ones of GERD patients tend to develop BE. The identification of those patients would facilitate surveillance programs to prevent esophageal cancer. Recent studies, have shown that duodenogastroesophageal reflux associated with delay in esophageal acid clearance time play an important role in the development of BE. The aim of our study is to evaluate and compare, using esophageal pH impedance, the esophageal clearance time and the frequency of acid and weakly acid reflux in patients with BE and mild erosive esophagitis. Twenty eight patients underwent esophageal pH impedance (14 with BE and 14 with mild erosive esophagitis), after the discontinuation of proton pump inibitors for, at least, ten days. We studied 11 men with mean age of 54,9 years in the BE group. In the erosive esophagitis group (nine patients classified as Los Angeles grade A and five grade B), five patients were men and the mean age was 47,9 years. The EB patients shown a prolonged total and upright esophageal clearence time for acid (p=0,003 and 0,014, respectively) and greater esophageal acid exposure (p=0,038) when compared to the erosive esophagitis ones. The number of acid and weakly acid reflux episodes were similar in both groups.